2008
DOI: 10.1111/j.1742-1241.2006.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of cyclins D1, E and cyclin-dependent kinase inhibitors p21waf1/cip1, p27kip1 in colorectal carcinoma: correlation with other cell cycle regulators (pRb, p53 and Ki-67 and PCNA) and clinicopathological features

Abstract: Aberrations in the cell cycle regulators are common features of many tumours and several have been shown to have prognostic significant in colorectal cancer. The expression patterns of cyclins D1 and E as well as cyclin-dependent kinase (CDK) inhibitors p21waf1/cip1 and p27kip1 and their interrelationship with other cell cycle checkpoint proteins [p53, pRb, Ki-67 and proliferative cell nuclear antigen (PCNA)] were investigated in colorectal cancer in order to ascertain coregulation and influence on tumour beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 43 publications
(131 reference statements)
6
58
1
3
Order By: Relevance
“…31 Cyclin D1 overexpression has been reported in laryngeal carcinoma and might be implicated in regulating cell proliferation by the critical G1/S checkpoint. 32 P63 is a p53 homolog and a potential oncogene in squamous cell cancer that has been found in the distal arm of 3q. 33 Loss of chromosomes 3p, 5q, 8p, 9p, 18q and 21q are commonly identified as well, where loss of 18q could indicate poor prognosis tumors.…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…31 Cyclin D1 overexpression has been reported in laryngeal carcinoma and might be implicated in regulating cell proliferation by the critical G1/S checkpoint. 32 P63 is a p53 homolog and a potential oncogene in squamous cell cancer that has been found in the distal arm of 3q. 33 Loss of chromosomes 3p, 5q, 8p, 9p, 18q and 21q are commonly identified as well, where loss of 18q could indicate poor prognosis tumors.…”
Section: Cytogenetic Alterationsmentioning
confidence: 99%
“…Several factors come into play in the regulation of cdk2 activity, such as binding of cdk2 inhibitors as p21 waf1 , p27 Kip1 , and p57 Kip2 (Malumbers and Barbacid, 2005), the already mentioned transient associations with cyclins A and E (Giordano et al, 1989(Giordano et al, , 1991Koff et al, 1992;Bates et al, 1994) and phosphorylation of specific tyrosine and threonine residues (Gu et al, 1992). The constitutive activation of cdk2/cyclin E complexes is often associated with the deregulation of G1 to S transition and tumor progression (Fujii et al, 1998;Harwell et al, 2004;Ioachim et al, 2004;Liao et al, 2004;Sunters et al, 2004;Peschos et al, 2005;Tenderenda, 2005). On these grounds, the targeting of cdk2 activity can have important implications for the development of therapeutics for cancer treatment.…”
mentioning
confidence: 99%
“…The detection of such markers may aid in risk stratification and cyclin E may be included in the list of possible candidates. The role of cyclin E in colon tumorgenesis is supported by certain studies which revealed overexpression of cyclin E in early stages of tumor development (17,23). Positive cyclin E staining was correlated with Ki-67 antigen (a marker of proliferative activity of malignant cells) and p53 protein level in these cells (3,24).…”
Section: A B Cmentioning
confidence: 69%